Effects of Overnight Oxidation on Perovskite Solar Cells with Co(III)TFSI Co-Doped Spiro-OMeTAD - Laxmi Nakka; Armin Gerhard Aberle; Fen Lin (Energies, 2022)
Metal-halide perovskite solar cells (PSCs) have achieved remarkable power conversion efficiencies in recent years, and spiro-OMeTAD plays a significant role as a hole transport material in PSCs with record efficiencies. However, further studies and systematic experimental procedures on doped spiro-OMeTAD are required to enable a reliable process for potential commercialization. In particular, the effect of the prolonged oxidation of Co(III)TFSI co-doped spiro-OMeTAD has been one of the unanswered topics in PSC research. In this work, we investigate the influence of overnight oxidation on the performance of PSCs with Co(III)TFSI co-doped spiro-OMeTAD. Co-doping spiro-OMeTAD with Co(III) complexes instantly oxidizes spiro-OMeTAD, leading to an improvement in power conversion efficiency (PCE) from 13.1% (LiTFSI-doped spiro-OMeTAD) to 17.6% (LiTFSI + Co(III)TFSI-doped spiro-OMeTAD). It is found that PSCs with spiro-OMeTAD co-doped with Co(III)TFSI without overnight oxidation could retain around 90% of the efficiency under maximum power point tracking at 1-sun illumination for 3000 min, whereas the efficiencies drop by more than 30% when Co(III)TFSI co-doped spiro-OMeTAD is exposed to overnight oxidation. Hence, it is important to inhibit the unnecessary overnight oxidation of Co(III)TFSI co-doped spiro-OMeTAD so as to save excess fabrication time and overcome the poor stability issues.